Sustainable extraction and purification of microalgae lipid using liquid biphasic flotation system for production of biofuel - Mat Aron, Nurul Syahirah (2024)
Microalgae are sustainable option for energy production due to its rich content in lipid, protein, and carbohydrate. Unlike the first and second generation biofuel, microalgae biofuel or known as the third generation has advantages of low-capital cost, more environmentally friendly as the cultivation of microalgae does not require input of freshwater and high energy intensity because it can be cultivated easily in an open pond. It also does not compete with food crop to gain a big open land and water for cultivation as well as nutrient input. However, the current processes of lipid extraction are energy intensive and requires high input of chemicals which are not eco-friendly. Therefore, this research unveils the potential of liquid biphasic flotation system in extracting lipid for biofuel production. It represents a holistic study on the effective method of microalgae cell wall rupture, and the maximum conditions for lipid extraction and purification using the liquid biphasic flotation system. In the first part of the study, the cell wall disruption was done on microalgae cell to ensure maximum recovery of lipid. Investigation on the effective paraments of cell rupture was done, the parameters were the duration of pre-treatment, duty cycle and the intensity of pre-treatment exposure on the microalgae cell. Highest lipid yield was recorded at duration of 1.5 min pre-treatment exposure, 80% duty cycle at 450 W microwave radiation. Following that, liquid biphasic flotation system was incorporated in the study to understand the ability of the system to recover lipid from microalgae. To achieve this, two types of mass separating agent were tested which were salt and sugar. In the first experiment, salt, namely ammonium sulphate was used. To understand the reliability of the integrated system (salting-out with liquid biphasic flotation), the lipid profile of the extractant was analysed using gas chromatography with flame ionization detection (GC-FID). Parameters such as types of alcohol, concentration of alcohol, concentration of microalgae, time of flotation, and lipid profile were investigated to understand to optimum conditions for maximum lipid extraction. Maximum lipid yield was seen when 100% concentration of ethanol, 50% concentration of microalgae, at 20 min flotation time were used. The upscaling of the system too showed a promising result. In the next experiment, sugar was used as the mass separating agent. The investigated parameters were types of sugar, ratio of the top-bottom phase, concentration of sugar and flotation time of the system. From this study, fructose achieved the highest lipid yield at a concentration of 150 g/L. The best ratio of lipid recovery was 2:1 at 15 min flotation time. This research saw a huge potential in liquid biphasic flotation technology in extracting lipid from microalgae. Apart from extracting lipid, this study also aimed to purify the extracted lipid. This was done by combining the liquid biphasic flotation system with a filter membrane technology. Different types and pore size of membrane were tested in the experiment. To see the effect of the filter membrane technology on lipid purification, the pressure of the vacuum pump was adjusted. From this experiment, PVDF 550 kDa showed a better performance in lipid purification process. Vacuum pump pressure of 80 kDa and 60 kDa showed a comparable result. Overall, under optimum operating parameters, this research managed to recover fatty acid methyl esters of C5:0, C10:0, C12:0, C14:0, and C20:0. Salting-out and sugaring-out LBF integrated system showed a great potential in extracting lipid. However, sugaring-out was observed to be suitable for shorter chain fatty acid methyl esters recovery, while salting out was seen to recover longer chain fatty acid methyl esters. While both is appropriate for biofuel production, but longer procedure is needed to process shorter fatty acid methyl esters to make it compatible for the application of biofuel. Exploration of effective and efficient method can be done in future study.